2018
DOI: 10.15829/1560-4071-2018-5-40-48
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Surgery Status and in-Hospital Complications of Coronary Bypass Grafting in Prediabetes and Type 2 Diabetes Patients

Abstract: Цель. Изучение предоперационного статуса и частоты госпитальных ослож-нений коронарного шунтирования у лиц с предиабетом в сравнении с пациен-тами с сахарным диабетом 2-го типа (СД 2) и нормогликемией. Материал и методы. Включены 708 последовательных пациента, подверг-шихся коронарному шунтированию (КШ) в 2011-2012гг в НИИ КПССЗ. При отсутствии ранее установленного СД и наличии пограничной гипергликемии пациентам проводился пероральный глюкозотолерантный тест (ПГТТ). Его результаты интерпретировались в соответ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
1
0
4
Order By: Relevance
“…Nevertheless, the results of prospective studies can serve as indirect evidence in favor of the adverse effect of prediabetes on the state of both the arterial wall as a whole and the severity of atherosclerotic changes in it [ 31 , 32 , 33 ]. So, in a recent national cohort study in Korea, with a 12-year prospective observation, it was shown that the DM group showed the highest incidence and risk of vascular complications (cardiovascular, renal; and retinal), followed by the IFG group and the lowest risk was in group of normoglycemia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results of prospective studies can serve as indirect evidence in favor of the adverse effect of prediabetes on the state of both the arterial wall as a whole and the severity of atherosclerotic changes in it [ 31 , 32 , 33 ]. So, in a recent national cohort study in Korea, with a 12-year prospective observation, it was shown that the DM group showed the highest incidence and risk of vascular complications (cardiovascular, renal; and retinal), followed by the IFG group and the lowest risk was in group of normoglycemia [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Учёными доказано, что активный скрининг перед коронарным шунтированием на дисгликемию позволяет дополнительно выявить около 9% пациентов с СД второго типа и 10% -предиабетом. Пациенты с предиабетом и СД второго типа имеют сопоставимый профиль госпитальных осложнений коронарного шунтирования, частота которых значимо превосходила таковую в группе без нарушений углеводного обмена [36]. Значение для развития субклинического атеросклероза имеет продолжительность предиабета [37], поскольку многие из атерогенных ФР уже присутствуют на предиабетической стадии [38].…”
Section: факторы риска и ассоциация с другими заболеваниямиunclassified
“…Несмотря на существующие рутинные методы выявления нарушений углеводного обмена, в том числе СД, до сих пор эта патология выявляется на поздних стадиях (при наличии манифестирующих осложнений). Это утверждение иллюстрируют данные российского регистра NATION [15], а также результаты многочисленных исследований среди пациентов, направляемых на коронарные вмешательства, где выявление ранее недиагностированного СД было обычным явлением [16,17].…”
Section: материал обзораunclassified